Aynuna: A Case Study of the Changing Functions of a Hijazi Coastal Settlement from the Nabatean to the Early Islamic Period - Juchniewicz, Karol (Études et Travaux, 2023)
A recent study proved that Aynuna has been settled since at least the Hellenistic period and was the major settlement on the Arabian coast of the northern Red Sea in the Nabatean/Roman period, serving as the port of Petra. Scientific literature is mostly concerned with the identification of Aynuna with ancient Leuke Kome, leaving aside the later history of the site. In the late Roman/Byzantine period its significance as a trade centre slowly diminished, although it might have remained a tax collection point. In the early Islamic period, Aynuna served as a local agricultural centre and war port for the Arabian forces conquering the Eastern Desert. Later on, accessibility of fresh water made it a stop on the Egyptian Hajj Route, and antique Aynuna/Leuke Kome finally became Islamic ‘Aynūna. This paper aims to present a diachronic analysis of the changing functions of the site using published archaeological reports and Arabic written sources.